The Role of Distress Tolerance in Non-Suicidal Self-Injury - Slabbert, Ashley Leonie (Curtin University, 2021)
Ashley’s PhD explored how an individual’s ability to tolerate distress may be related to their engagement in non-suicidal self-injury. Ashley’s PhD employed a range of experimental and self-report study designs, and involved the modification of a novel approach to assessing behavioural distress tolerance. The findings of this doctoral project suggest that perhaps one’s belief in their ability to tolerate distress is important, but separate to, their actual capacity to tolerate distress, and that self-perception may be more important in understanding non-suicidal self-injury.